dogmática constitucional; estado; estado constitucional de derechos y justicia; fines del estado; formulación normativa. - Pérez Carrillo, Juan Ramón (2024)
This theoretical reflection article analyzes the purposes of the Constitutional State of Rights and Justice in Ecuador, from a historical, legal and philosophical perspective, as well as the normative formulation of its constitutional dogmatics. With the use of a methodology anchored in a qualitative approach for a dogmatic legal typology, where the bibliographic review technique is used, based on the use of general and strictly legal methods, they allowed a comprehensive approach to the object of study. The results achieved reveal that the constitutional dogmatic of the purposes of the State in the 2008 Constitution lies in the change of a paradigm based on a more traditional approach focused on security and economic development towards a more inclusive vision oriented to human well-being, social justice and environmental sustainability. What allowed us to conclude that this transformation is the reflection of an evolution in the political and legal conceptions of the country and in the understanding of the role of the State, as well as a change in social priorities and values.